Effects of the metabotropic glutamate receptor 5 positive allosteric modulator CDPPB on rats tested with the paired associates learning task in touchscreen-equipped operant conditioning chambers - Lins, Brittney; Howland, J.G. (2016)
© 2015 Elsevier B.V. Effective treatments for the cognitive symptoms of schizophrenia are critically needed. Positive allosteric modulation (PAM) of metabotropic glutamate receptor subtype 5 (mGluR5) is one strategy currently under investigation to improve these symptoms. Examining cognition using touchscreen-equipped operant chambers may increase translation between preclinical and clinical research through analogous behavioral testing paradigms in rodents and humans. We used acute CDPPB (1-30mg/kg) treatment to examine the effects of mGluR5 PAM in the touchscreen paired associates learning (PAL) task using well-trained rats with and without co-administration of acute MK-801 (0.15mg/kg). CDPPB had no consistent effects on task performance when administered alone and failed to reverse the MK-801 induced impairments at any of the examined doses. Overall, the disruptive effects of MK-801 on PAL were consistent with previous research but increasing mGluR5 signaling is not beneficial in the PAL task. Future research should test whether administration of CDPPB during PAL acquisition increases performance.